2017
DOI: 10.1590/0103-6440201701098
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health-Related Quality of Life and Associated Factors in Brazilian Adolescents

Abstract: This study aimed to assess the impact of oral health on the quality of life of adolescents. A cross-sectional study was performed with students from public and private schools from Passo Fundo, Brazil. All students were aged between 15 and 19 years old. The proportional random sample consisted of 736 adolescents from 20 schools. A structured questionnaire was applied, and an oral examination was performed, counting the number of teeth. Oral health-related quality of life was assessed by OHIP-14. Associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 25 publications
4
59
0
1
Order By: Relevance
“…It is known that adolescents with self-reported halitosis have a negatively impacted quality of life [15,31], mainly in their social life, due to the constraints of daily communication [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that adolescents with self-reported halitosis have a negatively impacted quality of life [15,31], mainly in their social life, due to the constraints of daily communication [13].…”
Section: Discussionmentioning
confidence: 99%
“…Self-perceived oral health-related quality of life is a valid method to evaluate the impact of oral conditions in adults and children [15]. Halitosis has a negative effect on the individual's day-today life, affecting socialization and interpersonal relationships [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that caries experience and impact on OHRQoL in the presence of tooth pain were higher in adolescents who lived in suburban areas than in those living in central areas in a city in the interior of São Paulo 22 . Moreover, a higher impact on OHRQoL was also detected in high school students from public schools when compared to students from private schools 23 .…”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have used scales to assess the impact of oral diseases on the quality of life of the individuals. The OHIP-14 is a useful instrument to assess this impact (Afonso et al, 2017;Campos et al, 2014;Colussi, Hugo, Muniz, & Rösing, 2017;Oliveira et al, 2015;Silveira et al, 2014).…”
Section: Discussionmentioning
confidence: 99%